Speech intelligibility loss due to amyotrophic lateral sclerosis: the effect of tongue movement reduction on vowel and consonant acoustic features. - Rong, Panying; Usler, Evan; Rowe, Linda M.; Allison, Kristen; Woo, Jonghye; El Fakhri, Georges; Green, Jordan R. (Clinical Linguistics & Phonetics, 2021)
The purpose of this study was to identify aspects of impaired tongue motor performance that limit the ability to produce distinct speech sounds and contribute to reduced speech intelligibility in individuals with dysarthria secondary to amyotrophic lateral sclerosis (ALS). We analyzed simultaneously recorded tongue kinematic and acoustic data from 22 subjects during three target words (cat, dog, and took). The subjects included 11 participants with ALS and 11 healthy controls from the X-ray microbeam dysarthria database (Westbury, 1994). Novel measures were derived based on the range and speed of relative movement between two quasi-independent regions of the tongue – blade and dorsum – to characterize the global pattern of tongue dynamics. These "whole tongue" measures, along with the range and speed of single tongue regions, were compared across words, groups (ALS vs. control), and measure types (whole tongue vs. tongue blade vs. tongue dorsum). Reduced range and speed of both global and regional tongue movements were found in participants with ALS relative to healthy controls, reflecting impaired tongue motor performance in ALS. The extent of impairment, however, varied across words and measure types. Compared with the regional tongue measures, the whole tongue measures showed more consistent disease-related changes across the target words and were more robust predictors of speech intelligibility. Furthermore, these whole tongue measures were correlated with various word-specific acoustic features associated with intelligibility decline in ALS, suggesting that impaired tongue movement likely contributes to reduced phonetic distinctiveness of both vowels and consonants that underlie speech intelligibility decline in ALS.